What transformations change the graph of f(x) to the graph of g(x)? f(x) = –7x² g(x) = –35x² + 5 (1 point) The graph of g(x) is the graph of f(x) stre?

What transformations change the graph of f(x) to the graph of g(x)? f(x) = –7x² g(x) = –35x² + 5 (1 point) The graph of g(x) is the graph of f(x) stre?

Related Answers

Explore the latest questions and answers related to "What transformations change the graph of f(x) to the graph of g(x)? f(x) = –7x² g(x) = –35x² + 5 (1 point) The graph of g(x) is the graph of f(x) stre?"

Answered: What is 4x-7x +5x =

Assume X represents an apple: Allen gave you 4 apples, Shon gave you 5 apples, and Andy took 7 apples, how many apples remain ? I hope you agree that the answer is 2 (Mathematically it reads 2X) Note that Give = plus (cause it adds to stock) and Take = minus (cause it reduces your stock)

Answered: 7x=5y Find the slope intercept equation for the line with the indicated

The general form of equation of line is y= mx+c here M is the slope and c represents intercept m is also given as tan(theta) where theta is the angle of incidence.

Answered: What is the intersection for 72= 9x+ 8y and 28=-7x-4y?

At the intersection of those 2 lines the X and the y are equal. 72 = 9x + 8y 28 = -7x -4y ------------------ If you multiply the 2nd equation by 2 you'll get -8y and when you add both equations the y will 'dissapear"...... 72 = 9x + 8y 56 = -14x -8y ------------------ 128 = -5x x = -25.6 Now ...

Answered: (7 - x = 4) how to show your work?

Or you can subtract 7 from both sides: 7-x-7 = 4-7 gives -x = -3, then multiply both sides by -1 to get x = 3.

Answered: How do you figure out -3/5 X 5 1/5?

One way is to change 5 1/5 into an improper fraction 26/5. Then -3/5 x 26/5 = -78/25 = -3 3/25 = -3.12 Or you could start with decimals: -.6 x 5.2 = -3.12

Answered: How can I change my address?

The easiest way is to move. If you cannot afford to move, then joining the military or robbing a bank provide alternatives for some.
Liked this question? Tell your friends about it

More Questions

How to solve: (x + 6) -1 (2x + 7) -3x = -9

Hi Lisa (x + 6) -1*(2x + 7) -3x = -9 X + 6 -2X -7 -3X = -9 -4X -1 = -9 4X = 8 X = 2 Let us check uf the answer is correct (put 2 instead of X and check if it balances: (2+ 6) -1 (2*2 + 7) -3*2 = -9 8 -1*( 4 +7) -6 = -9 8 -11 -6 = -9 -9 = -9 Yes it balnces. So the answer is OK. If ...

Y/2+x;use x=1,and y=2

2/2 + 1 = 2

How do you graph 5 < x?

You can put the value of x and plot in the graph paper.Want to get more information you can take online tutoring service from site like Tutorpace.

What would that be in usa

What is it anywhere?